THE PROBLEMATIC ENGLISH TEACHING LEARNING IN GRADE VII JUNIOR HIGH PONDOK PESANTREN AL-MARHAMAH PUTRA - Dwisetyo, Vici; Luardini, Maria Arina; Perdana, Indra (Journal Compound: Improving the Quality of English Education, 2022)
This research is revealing how the English run in the Pondok Pesantren Al-Marhamah grade VII Junior High, what student had to do, what they could expect, and what teacher expected from them. The researcher conducted the research in order to know the process of teaching and learning process, as the low vocabulary occurred in Pondok Pesantren Al-Marhamah Putra grade VII. The researcher did the research by using observation, interview and documentation as research instruments. Observation was used to know the process of teaching and learning at Pondok Pesantren Al-Marhamah Putra grade VII. In observation, the researcher observed student and environment Pondok Pesantren Al-Marhamah Putra grade VII. Then, the researcher interviewed students in Pondok Pesantren Al-Marhamah Putra grade VII. The researcher describe the the way teaching and learning in Pondok Pesantren Al-Marhamah grade VII. While documentation held to see the lesson plan that available in there as teaching guidance. The interview conduct as teacher and student point of view of their teaching learning activity. Observation, documentation, and interview show that English teaching learning in this Pondok Pesantren is problematic. First, the English teacher unqualified. Second, uncondusive equipment to teaching and learning. Third, the environment still not support the daily use of English. The continuation become recommendation to overcome problematic English teaching learning in grade VII.